Elliptic particles in the Holy Qurʼān: Implications on English Translation Accuracy and Understanding of Selected Verses - Abeer Dglan; Abdul-Qader Khaleel Mohammed Abdul-Ghafour; Abdulhameed Ashujaa; Abdusalam Mohammed Al-Ghrafy (Hasanuddin University, 2025)
This paper focuses on the challenge of translating elliptic particles in the Holy Qurʼān, a subtle linguistic feature often overlooked by translators due to its implicit nature. Elliptic particles pose significant challenges for translators, given that they are not always immediately apparent and require deep reading of Qurʼānic exegeses. Although there are many studies on Qurʼānic ellipsis, the specific focus on elliptic particles remains scarce. The present paper fills this gap by examining how elliptic particles are rendered in selected English translations of selected verses and evaluating the strategies employed in terms of accuracy and clarity. Through qualitative content analysis and comparative evaluation of three key English translations of twelve selected verses, the study findings revealed that while literal translation was predominantly used and often ensured precise and comprehensible renditions, it in a few cases resulted in misconceptions. In contrast, explicitation strategy offers enhanced clarity and readability. These findings thus contribute to the field of translation studies by underlining the need for a balance between fidelity to the original text and accessibility of the translation. The findings also suggest that translation strategies must carefully account for both linguistic precision and reader comprehension to ensure accurate delivery of the Qurʼānic message.